ANALISIS MINAT BELI TERHADAP PRODUK FASHION MEWAH PALSU - Yudhistira Putra Wardhana (2020)
This study examines the purchase intenion of consumers in counterfeit luxury fashion products. The purpose of this study is to find out what influences people's buying interest in artificial luxury fashion products, this study includes social media influencers, hedonic shopping motivation, and brand equity. The approach used in this research is descriptive and verification. The type of data used in this study is quantitative data and uses primary and secondary data sources. The population in this study are people who live or do activities in Jabodetabek. The sample in this study are 175 people with probability sampling technique. The questionnaire method was carried out in collecting data. Data analysis techniques were processed using the Structural Equation Model (SEM) approach based on Partial Least Square (PLS). The results of data analysis show that: (1) influencer's social media does not affect buying interest with a value of t count 1.728 <t_table 1.973 and a significance level of 0.085> 0.05; (2) hedonic shopping motivation influences buying interest with a value of t count 2.713> t table with a significance level of 0.007 <0.05; (3) brand equity influences buying interest with a value of t count 8.106> t table 1.973 and a significance value of 0.000 <0.05. The coefficient of determination R2 of 0.657 means that the contribution of influencer social media variables, hedonic shopping motivation and brand equity to buying interest is 65.7%, while the remaining 34.3% contribution to the purchase interest variable is filled by other variables besides influencer social media, hedonic shopping motivation and brand equity.